1991
DOI: 10.1148/radiology.178.1.1984294
|View full text |Cite
|
Sign up to set email alerts
|

Invasive lobular carcinoma: mammographic findings in a 10-year experience.

Abstract: From January 1, 1976 to December 30, 1985, 1,966 cases of breast carcinoma were diagnosed and treated at Malmo General Hospital, Malmo, Sweden. Of these cases, 185 (9.4%) involved invasive lobular carcinoma (ILC). Mammography in 137 cases demonstrated the following findings: spiculated opacity (53%), architectural distortion (16%), poorly defined opacity (7%), normal or benign findings (16%), and parenchymal asymmetry (4%). Radiographic definition of the ILC lesion varied greatly with projection: The craniocau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
118
3
9

Year Published

1993
1993
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 214 publications
(139 citation statements)
references
References 0 publications
9
118
3
9
Order By: Relevance
“…We found that 11 cases (29%) manifested as only asymmetrical density, and 16 cases (42%) presented with mass and/or architectural distortions. Even large tumors may be undetectable by physical examination and mammography (26). Supporting this point, one of our cases with a 4-cm tumor that was found upon histopathologic assessment was undetectable by physical examination and mammography and could only be detected by sonography.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…We found that 11 cases (29%) manifested as only asymmetrical density, and 16 cases (42%) presented with mass and/or architectural distortions. Even large tumors may be undetectable by physical examination and mammography (26). Supporting this point, one of our cases with a 4-cm tumor that was found upon histopathologic assessment was undetectable by physical examination and mammography and could only be detected by sonography.…”
Section: Discussionsupporting
confidence: 75%
“…Characteristically, tumor cells surround the ducts without obstructing them. It is postulated that the lack of ductal invasion or obstruction may explain the low rates of microcalcifications associated with ILC (26). In our study, five out of 38 ILC cases (15%) showed clusters of microcalcifications that were consistent with BIRADS category 4-5.…”
Section: Discussionsupporting
confidence: 44%
See 3 more Smart Citations